Fundamentals of Entrepreneurship ENT300 Business Plan Report Business Name: PS Enterprise / Nur Athiqah Meor Hamdan - Meor Hamdan, Nur Athiqah (2019)
The company’s name is PS Enterprise. PS stands for Power Supply Enterprise. The idea for the company’s name comes from our ideas to show that we are innovators of electrical appliances. PS Enterprise established under Sole Proprietorship Business Act 1956. The nature business of PS Enterprise is to produce products that can make someone life easier in preparing the most important meal of the day. PS Enterprise produce Wifey Material Tool which is a convenient appliance that contains multi-functions breakfast maker which saves time as it consists of 4 different kitchen appliances in 1 product. PS Enterprise is a manufacturing company that produce product that is based on electrical appliances.